Spatial distribution and its driving forces analysis of soil organic matter in semi-arid grassland open-pit mining areas - Wu, Zhenhua; Wang, Xiaoying; Dai, Ziqiang; Ma, Weibo; Yang, Dejun; Yang, Yongjun; Yu, Qiao (Journal of Environmental Engineering and Landscape Management, 2024)
Studying the spatial distribution of soil organic matter (SOM) and exploring its driving factors in semi-arid grassland open-pit coal mining areas is crucial for sustaining ecological development and security. Currently, research on SOM in mining areas lacks large-scale investigation, sampling, spatial distribution, and driving force research for semi-arid grassland open-pit coal mining areas, and it is unable to comprehensively grasp the distribution characteristics and driving force of SOM in open-pit coal mines. In view of this, this study took the Shengli Coal Field in Xilinhot City, the hinterland of Xilingol Grassland, as an example to research the spatial distribution and driving forces of SOM in the semi-arid grassland open-pit coal mining area. The results show that: (1) Areas with high SOM content were mainly distributed in the north of open-pit germanium mine, west No. 2 open-pit mine, and No. 1 open-pit mine. Areas with low SOM content were mainly distributed on the east and southeast sides of the city. From the spatial distribution perspective, mining has a certain impact on SOM in the study area. (2) Natural factors have a higher impact on SOM changes than human factors. The order of influence degree of each factor on the spatial distribution of SOM is NDVI > Water > Agriculture > Mine > Town > Industry. The sources of influence on SOM in the research area are relatively complex. (3) The interaction between two factors presents two relationships: nonlinear enhancement and dual-factor enhancement. A single factor is lower than the interaction between various factors. In the interaction between factors, the explanation rate of interaction between Town, Agriculture, Mine, NDVI, Water, and all other factors is above 0.85. This study has important practical significance for soil management in mining areas, ecological restoration, and planning of national land space, etc.